ANALISIS ABC DALAM PERENCANAAN OBAT GOLONGAN ANTIBIOTIK DI INSTALASI FARMASI RAWAT INAP RSU X DENPASAR - Oviani Gusti Ayu; Listiani Putu Ayu Ratih; Cahyani Ni Gusti Ayu Dwi (Institut Teknologi dan Kesehatan Bintang Persada, 2023)
Planning and procurement of drugs is one of the important functions in the logistics management stage of drugs, including antibiotic drugs. A good management system will ensure the availability of drugs according to patient needs. The purpose of the study was to determine the ABC analysis based on use value and investment value in planning antibiotic class drugs at the Inpatient Pharmacy Installation of RSU X Denpasar. This type of research is descriptive non-experimental using quantitative data. The data is obtained from a review of reports or systems, data in the form of reports on the types of antibiotic class drugs used in the 2021 period, reports on the number of antibiotic class drugs used and reports on the price of antibiotic drugs. The value of using antibiotics was group A consisting of 29 items (27.35%) with a total usage of 72,591 items (79.42%); group B consisted of 26 items (24.52%) with a total usage of 14,197 items (15.53%); group C consisted of 51 items (48.11%) with a total usage of 4,613 items (5.04%). The investment value for antibiotics is group A consisting of 17 items (16.03%) with a total investment of IDR 6,414,357,620 (79.94%); group B consists of 20 items (18.86%) with a total investment of IDR 1,193,164,115.00 (14.86%); group C consisted of 69 items (65.09%) with a total investment of IDR 417,102,141.50 (5.20%).